2020
DOI: 10.1016/j.apnu.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of nurses and midwives due to COVID-19 outbreak: The case of Turkey

Abstract: The study was carried out to determine the psychological impact levels of nurses and midwives due to the COVID-19 outbreak. Methods: The research is planned in a descriptive type. Nurses and midwives working in any health institution in Turkey constituted the population of the research. The questionnaire form of the study was shared on social media tools between 01 and 14 April 2020 and a total of 758 nurses and midwives were included in the study sample. Personal Information Form, State-Trait Anxiety Inventor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
106
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(139 citation statements)
references
References 37 publications
19
106
0
14
Order By: Relevance
“…The overall pooled point estimates of prevalence for anxiety varied between 8% and 91%, which was reported by 73 studies [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [28] , [29] , [30] , 32 , 34 , 35 , [37] , [38] , [39] , [42] , [43] , [44] , [45] , [46] , 48 , 49 , 51 , [53] , [54] , [55] , [56] , [57] , 62 , [64] , [65] , [66] , [67] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] ,…”
Section: Resultsmentioning
confidence: 99%
“…The overall pooled point estimates of prevalence for anxiety varied between 8% and 91%, which was reported by 73 studies [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [28] , [29] , [30] , 32 , 34 , 35 , [37] , [38] , [39] , [42] , [43] , [44] , [45] , [46] , 48 , 49 , 51 , [53] , [54] , [55] , [56] , [57] , 62 , [64] , [65] , [66] , [67] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] ,…”
Section: Resultsmentioning
confidence: 99%
“…In their qualitative study Kackin et al 37 examined the psychosocial problems of nurses who cared for patients diagnosed with COVID-19 and found that nurses were adversely affected by the pandemic process with feeling fear and showing depressive symptoms. Aksoy and Koçak 38 stated that the most intense feeling due to COVID-19 among nurses who work in healthcare services was the feeling of fear. In Thailand, a study conducted by Apisarnthanarak et al, 39 that evaluated the emotions of healthcare professionals for pandemic reported that 90% of them were fearful of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for psychological problems among Frontline nurses were fear of infecting her family (71.9%), not meeting with her family (7.1%). Missing her family (21.%5), decreased work ef iciency due to Fear of transmission (75.9%), reduced care of patients due to fear of communication (9.1%), Tiring, and inadequate productive work because of no protective equipment (5.0%) (Aksoy and Koçak, 2020). The similar reasons for psychological problems nurses was identi ied and discussed by another study in that 60% of the registered nurses felt they were not personally well-prepared to handle the outbreak, and it could be the additional causes for producing fear and stress among nurses (Tayyib and Alsolami, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…According to the analysis, (36.3%) felt Anxiety, (31.3%) experienced uneasiness and 19.4% felt fear due to COVID-19. The participants were having fear, anxiety, depression and 49.7% of said that they experienced remorse about their profession (Aksoy and Koçak, 2020).…”
Section: Psychological Impacts Among Nursesmentioning
confidence: 99%